2012
DOI: 10.1111/1574-6968.12005
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene,ardD, determines antirestriction activity of the non-conjugative transposon Tn5053and is located antisense within thetniAgene

Abstract: The mercury-resistance transposon Tn5053 inhibits restriction activity of the type I restriction-modification endonuclease EcoKI in Escherichia coli K12 cells. This is the first report of antirestriction activity of a non-conjugative transposon. The gene (ardD) coding for the antirestriction protein has been cloned. The ardD gene is located within the tniA gene, coding for transposase, on the complementary strand. The direction of transcription is opposite to transcription of the tniA gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 9 publications
(18 reference statements)
1
17
0
Order By: Relevance
“…On the contrary, bacterial genome annotation programs systematically remove overlapping genes [ 73 , 79 81 ], thereby efficiently preventing their discovery. Perhaps it is not surprising that with the exception of E. coli ’s three overlapping genes, only a few further examples have been discovered rather accidentally in Streptomyces [ 82 ], Pseudomonas [ 83 , 84 ] or Xanthomonas [ 85 ]. Functional analyses of overlapping genes in bacteria are even rarer.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, bacterial genome annotation programs systematically remove overlapping genes [ 73 , 79 81 ], thereby efficiently preventing their discovery. Perhaps it is not surprising that with the exception of E. coli ’s three overlapping genes, only a few further examples have been discovered rather accidentally in Streptomyces [ 82 ], Pseudomonas [ 83 , 84 ] or Xanthomonas [ 85 ]. Functional analyses of overlapping genes in bacteria are even rarer.…”
Section: Discussionmentioning
confidence: 99%
“…The merA gene encodes for a reductase that reduces Hg 2+ to Hg 0 [27]. The tniA transposase gene is usually present in integrons and composite transposons conferring antibiotic resistance [29]. The S. enterica Indiana strain MHYL genome carries genes conferring resistance to β-lactams, amide alcohols, tetracyclines, aminoglycosides, and sulfonamides.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, statistical analysis of bacterial genomes has shown that ORFs overlapping annotated genes in alternative reading frames are longer than expected, leading to the hypothesis of a potential selection pressure due to overlapping protein-coding genes (Mir et al, 2012). Besides this, functionality of at least a few non-trivially overlapping genes has been demonstrated (e.g., Behrens et al, 2002;Balabanov et al, 2012).…”
Section: Introductionmentioning
confidence: 99%